Glomerular filtration rate estimated using creatinine, cystatin C or both markers and the risk of clinical events in HIV‐infected individuals. Issue 2 (11th September 2013) - Lucas, GM; Cozzi‐Lepri, A; Wyatt, CM; Post, FA; Bormann, AM; Crum‐Cianflone, NF; Ross, MJ; ,
<x xml:space="preserve">Abstract</x> Objectives The accuracy and precision of glomerular filtration rate (GFR) estimating equations based on plasma creatinine (GFRcr), cystatin C (GFRcys) and the combination of these markers (GFRcr‐cys) have recently been assessed in HIV‐infected individuals. We assessed the associations of GFR, estimated by these three equations, with clinical events in HIV‐infected individuals. Methods We compared the associations of baseline GFRcr, GFRcys and GFRcr‐cys [using the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) equations] with mortality, cardiovascular events (CVEs) and opportunistic diseases (ODs) in the Strategies for the Management of Antiretroviral Therapy (SMART) study. We used Cox proportional hazards models to estimate unadjusted and adjusted hazard ratios per standard deviation (SD) change in GFR. Results A total of 4614 subjects from the SMART trial with available baseline creatinine and cystatin C data were included in this analysis. Of these, 99 died, 111 had a CVE and 121 had an OD. GFRcys was weakly to moderately correlated with HIV RNA, CD4 cell count, high‐sensitivity C‐reactive protein, interleukin‐6, and D‐dimer, while GFRcr had little or no correlation with these factors. GFRcys had the strongest associations with the three clinical outcomes, followed closely by GFRcr‐cys, with GFRcr having the weakest associations with clinical outcomes. In a model adjusting for demographics, cardiovascular risk factors, HIV‐related factors and inflammation markers, a 1‐SD lower GFRcys was associated with a 55% [95% confidence interval (CI) 27−90%] increased risk of mortality, a 21% (95% CI 0−47%) increased risk of CVE, and a 22% (95% CI 0−48%) increased risk of OD. Conclusions Of the three CKD‐EPI GFR equations, GFRcys had the strongest associations with mortality, CVE and OD.